Promoting fruit and vegetable consumption during the COVID-19 pandemic - SportStudisMoveYou (SSMY): A randomized controlled trial - Joram Weber; Claudio R. Nigg (AIMS Press, 2022)
Background: The stay-at-home circumstances due to the global coronavirus pandemic have had some negative impacts on people's eating behavior. Purpose: Therefore, this study attempted to improve fruit and vegetable (FV) consumption intention and behavior through an online video intervention based on the social cognitive theory. Methods: Participants were recruited with a promotion video posted on social media channels. After consenting and completing a pre-survey, participants were randomly assigned to either a) the intervention group addressing FV consumption or the b) attention control group addressing physical activity. After two weeks, the participants completed an online post-survey. Results: The participants (N = 82) were 77% female and 50% students; 95% chose German for the survey language, and 84% were from Switzerland. The mean baseline FV consumption intention was 3.05 (standard deviation: 1.03), and FV consumption was 4.64 (standard deviation: 2.06) portions a day. The analysis showed no significant change in FV consumption intention (F = (1, 78) = 0.02, p = 0.88, ηp2 = 0.00) or behavior (F = (1, 78) = 0.019, p = 0.89, ηp2 = 0.03) due to the intervention. Conclusions: Plausible reasons why no significant effect was found were the brief intervention duration, the setting and insufficient tailoring. The lessons learned from this study are to plan better, tailor more to the needs of participants and carefully consider the goals before promoting an intervention.